2020
DOI: 10.1371/journal.pone.0227700
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic thermal manipulation has short and long-term effects on the development and the physiology of the Japanese quail

Abstract: In vertebrates, the embryonic environment is known to affect the development and the health of individuals. In broiler chickens, the thermal-manipulation (TM) of eggs during the incubation period was shown to improve heat tolerance at slaughter age (35 days of age) in association with several modifications at the molecular, metabolic and physiological levels. However, little is known about the Japanese quail (Coturnix japonica), a closely related avian species widely used as a laboratory animal model and farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 63 publications
8
34
1
1
Order By: Relevance
“…The chicks cloacal temperature in the CIT group was signi cantly (p≤0.05) increased compared with control as indicated by (Abuoghaba, 2017) suggesting that heat stress caused internal temperature dysregulation. The achieved results showed no impact of thermal manipulation during quail's embryogenesis in embryonic mortality and hatchability percentages similar results were obtained in previous studies in quails (Alkan et al, 2013;Vitorino Carvalho et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…The chicks cloacal temperature in the CIT group was signi cantly (p≤0.05) increased compared with control as indicated by (Abuoghaba, 2017) suggesting that heat stress caused internal temperature dysregulation. The achieved results showed no impact of thermal manipulation during quail's embryogenesis in embryonic mortality and hatchability percentages similar results were obtained in previous studies in quails (Alkan et al, 2013;Vitorino Carvalho et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Compared to controls, TM chicks were found to have a reduced hatchability rate in the current study. In other avian species like ostriches and Japanese quail, TM resulted in a similarly decreased hatchability rate [39,40]. However, mixed findings were reported for the effect of TM on broiler hatchability, as some studies found that TM positively or negatively affected the hatchability rate [31,[41][42][43], while others reported no effect [36,[43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, fine-tuning egg incubation temperature has been used to develop strategies to help chickens better withstand heat later in life (Loyau et al, 2015). TM has since been studied in several other avian species, including turkeys for thermoregulation and muscle growth (Maltby et al, 2004;Piestun et al, 2015), ducks for the lipid metabolism and liver (Wang et al, 2014;Massimino et al, 2019), and quail for growth, physiological and metabolic parameters (Vitorino Carvalho et al, 2020).…”
Section: Temperature Programming Strategies Temperature Increases During Egg Incubationmentioning
confidence: 99%